PERANCANGAN POLA BARU PEMASARAN USAHA FASHION DI INDONESIA MELALUI FENOMENA CITAYAM FASHION WEEK (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
The Citayam Fashion Week phenomenon is a phenomenon that in recent months has become a hot topic of conversation among Indonesian people. This phenomenon is a phenomenon where teenagers from Jakarta and the surrounding area gather on Jalan Sudirman to show off their outfits or clothes to the general public. This phenomenon raises the economic potential to develop fashion SMEs in Indonesia. The purpose of this research is to design the concept of marketing and business branding in fashion SMEs in Indonesia. The research method used is descriptive qualitative with a literature and literature study approach. The results of this study are in the form of marketing and branding patterns in fashion SMEs. Not only that, this study also describes the landscape of the marketing and branding ecosystem for fashion SMEs in the era of the Citayam Fashion Week phenomenon